An investigation of how enquiry-based fieldwork develops action competence in Grade 12 Geography: a Namibian case study,Investigating opportunities for the development of action competence through fieldwork in the Namibian senior secondary school Geography curriculum - Simasiku, Frederick (Rhodes University, Faculty of Education, Department of Education, 2012)
The goal of the study was twofold: firstly to investigate and describe how senior secondary school geography teachers were implementing enquiry-based learning through fieldwork. Secondly, to investigate and document how enquiry-based learning through fieldwork facilitated the development of action competence amongst learners in a geography classroom. In order to address the first goal, a survey questionnaire was utilised to generate descriptive data from a sample of seven geography teachers in the Hardap region of Namibia. Although teachers engaged learners with enquiry-based fieldwork learning activities it is suggested, based on the findings of data of this goal, that teachers face severe limitations in terms of integrating environmental learning into the geography curriculum. The main limitations of the teachers include: limited practical knowledge of and training in how to teach fieldwork skills; a lack of teaching resource materials; time constraints; heavy personal loads; and lack of school support for environmental education. In addressing the second goal an enquiry-based fieldwork learning unit was planned and implemented in the researcher's classroom. Observation, focus group interviews, and audio records of learning interactions, were used as data generation methods for this cycle of the study. An indicator framework for identifying action competence in learners was constructed as a data analysis tool. In terms of the findings of goal two it is evident that enquiry-based learning through fieldwork facilitated the development of action competence amongst learners. Six overarching benefits of this type of learning were identified in this study, namely: - It empowered learners to develop contextual knowledge and understanding of issues that they investigated. - It facilitated commitment thus motivated learners to take indirect action. - It promoted social interaction and group cohesion amongst learners thus enhanced their decision-making ability for problem-solving and action taking. - It elicited emotional responses and a greater understanding of learners' own and others' attitudes and values towards issues. - It fostered critical thinking thus permitted learners to envisage a future based on their learning experiences. - It enabled learners to plan and take indirect action during the learning process. Based on the research findings, some lessons learned are presented in an attempt to contribute to the effective implementation of enquiry-based fieldwork at the classroom level.
Keywords: Competency-based education -- Namibia -- Hardap; Geography -- Study and teaching (Secondary) -- Namibia -- Hardap; Student-centered learning -- Namibia -- Hardap; Active learning -- Namibia -- Hardap; Environmental education -- Namibia -- Hardap; Environmental education -- Activity programs -- Namibia -- Hardap